MASA SIMPAN ANEKA SAMBAL DARI BAHAN NABATI MENGGUNAKAN METODE ACCELERATED SHELF LIFE TESTING: KAJIAN LITERATUR - Yunita Siti Mardhiyyah; Irawati Ningsih (AGROINTEK, 2021)
Sambal or sauce is a supplementary ingredient that dominates the market. But, many products do not include an expiration period. Sambal sauce generally can not be consumed once, so it needs storage to be more durable. The main damage is characterized by changes in physical, chemical, biological, and organoleptic characteristics. Various studies on the shelf life of chili sauce have been carried out, so the purpose of this study is to identify, analyze, and compare literature sources in the form of research results that show the effect of temperature differences on the chemical, microbiological and organoleptic properties of various chili sauces, so it is expected to be useful for serve as a reference for efforts to control damage to sauces or chili sauce by making the best storage. There are 5 groups of chili sauce, they are chili sauce, tomato sauce, onion chili sauce, fruit sauce, and andaliman sambal. The chili sauce is stored in three different temperatures (low, room and high temperatures) with the Accelerated Shelf Life Test (ASLT) method and Arrhenius model. Based on the results of the study, there is a low temperature storage of chili sauce last longer than room temperature and high storage that is 34-170 days. Whereas at room temperature and high temperature storage each lasted for 23-98 days and 21-54 days.